Curling Crunch - Jake Maddox (Stone Arch Books, 2023)
Maisie loves pitching for her softball team in Arizona, so she's crushed when she has to move to Minnesota to live with her dad. Upset about the move and her parents' divorce, Maisie isn't thrilled when her dad asks her to join his curling team. She thinks it's a strange sport. But as she learns more about curling--and how much her dad loves it--she begins to have a change of heart. But when its crunch time for the team, will Maisie be able to take charge and lead? Find out in this exciting, easy-to-read chapter book by Jake Maddox!
Keywords: Sport Stories -- Sport Stories